A NEW INTELLIGENT DRIVER VIGILANCE SYSTEM DESIGN USING TILT SENSORS - Ali Zuhair Ghazi Zahid; Karrar Shakir Muttair; Oras Ahmed Shareef; Abbas Ali Diwan; Hazeem Baqir Taher; Raed Hameed Chyad Alfilh; Ahmed Mahmood Farhan; Mahmood Farhan Mosleh; Faiz Arith (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
A significant number of causes for people killed by automobile accidents on both public and interior roads are the driver's failure to pay attention to the roadway, as well as other factors such as tiredness, sleep during driving, using the phone, or even the driver being intoxicated, etc. This work aims to identify sleepy status, pinpoint the onset of sleep, and alert the driver when their level of alertness drops below a level that does not improve productivity or the vehicle's overall safety protocols to prevent drowsiness-related crashes. In this article, we present a new method for implementing drowsiness detection inexpensively, using a Raspberry Pi as a central processor board that connects all practical measurement components. In addition, the proposed method includes the following activities: tracking the driver's head vibration while driving using tilt sensors. Moreover, a camera was mounted in front of the driver to take photos and record videos of the driver's health. As a result, the results were entirely satisfactory, and if the driver was operating the vehicle while fatigued, the response was 95% reliable and fast.